Acoustic Properties of FeCl3 in Water at different Temperatures - Arbad, B.R.; Patil, C.S.; Shankarwar, A.G. (Asian Journal of Chemistry, 2010)
Apparent molar volume (φv) and compressibility study of FeCl3 in water, in the concentration range of 0.04 to 0.2 M at different temperatures have been computed from measured sound velocities and densities. The limiting values of φv (φvo) , φk, (φko) and their concentration variations are explained on the basis of solute-solvent interactions.